WATER QUALITY INDICATOR BACTERIA IN BENGAWAN SOLO AND PORONG RIVERS AND THEIR ESTUARIES - Thayib, Soeminarti S.; Ruyitno, -; Kunarso, Djoko Hadi; Razak, Hamidah (Marine Research in Indonesia, 1989)
Water samples taken from rivers and estuaries stations in Bengawan Solo and Porong rivers in East Java were analyzed for the pollution of indicator bacteria in July-August and NovemberDecember 1984, to determine the influences of domestic wastes on the quality of these waters. Higher frequency of occurrences of high total coliform, fecal coli and fecal streptococci were observed in water samples collected in river stations, river mouths and in the vicinity of dense populated areas. The distribution of saprophytes, freshwater bacteria and indicator bacteria were also studied. The changes in the bacterial population as funciton of the salinity were shown during the observations. Some pathogenic bacteria like Salmonella, Yarsinia, and Vibrio parahaemolyticus and others have been isolated from waste and mud samples.